Pengaruh Keselamatan, Kesehatan dan Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan PDAM Tirtana Di Provinsi Sumatera Utara - Sri Elny; Julkarnain Julkarnain; Iriani Iriani (Universitas Nusantara PGRI Kediri, 2023)
At this time companies are competing to achieve their goals, therefore the company is trying to manage human resources well. One of the good HR management is by paying attention to the safety and health of its employees. In addition to occupational safety and health, the company must also pay attention to and be responsible for maintaining the quality of work life and fostering the workforce so that they are willing to contribute optimally to achieve company goals. Quality of work life is a concept or management philosophy in order to improve the quality of human resources which has been known since the decade of the seventies. Quality of work life is a major issue that deserves the attention of the organization. The purpose of this study was to find out how the influence of occupational safety and health and the quality of work life on the employee performance of PDAM Tirtanadi, North Sumatra Province. The population in this study is all employees, totaling 432 people and the sample in this study amounted to 43 employees at PDAM Tirtanadi, North Sumatra Province. The results showed that Occupational Safety and Health had a positive and significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. Quality of Work Life has a positive and significant effect on the performance of PDAM Tirtanadi employees, North Sumatra Province. Based on the significance test simultaneously on Occupational Safety and Health and Quality of Work Life together or simultaneously have a positive and significant effect on employee performance.